Electron transfer by singlet excited state of porphyn and electron acceptor affinity in rigid medium: photoacoustic phase angle analysis - CORNÉLIO,Marinônio Lopes (1997)
Photoacoustic spectroscopy provides information about both amplitude and phase of the response of a system to an optical excitation process. This paper presents the studies of the phase in the electron transfer process between octaethylporphyn (OEP) and quinone molecules dispersed in a polymeric matrix. It was observed a tendency in the phase behavior to small values only in the spectral region near to 620 nm, while for shorter wavelength did not show any tendency. These measurements suggested that the electron transfer to acceptor occurred with the participation of octaethylporphyn singlet excited state.